KERANGKA METODOLOGI KAJIAN RESISTENSI PEREMPUAN PEMBACA NOVEL CHICK LITERATURE PADA APLIKASI WATTPAD - Fatmawati, Endang (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
This paper aims to offer a methodological framework for the study of resistance of female readers of the chick lit novel on Wattpad. It is hoped that the methodological framework will become the basis for other re- searchers to continue to research. An example of the object of study is the novel Prejudice meets Pride with the production of literary works and various genres. The critical contextualist approach was conceptualized by the author to examine resistance, focus on context, and with dialogic validity whose characteristics include truthfulness, self reflexivity, and polivocality.